User perceptions on the privacy of health information - Lehto, Miikael (2016)
Activity trackers have become more common and they enable the collection of information about an individual’s physical activities and health. Traditionally a person’s health information was stored in the health care provider’s databases, but now health information is being stored in multiple services. This change has brought new ways to utilize technologies in the area of health and wellness, but at the same time questions have surfaced concerning the privacy of an individual’s information. This thesis discusses a study regarding the user perception on the privacy and sensitivity of health information collected with wearable devices. The study also explored the user perception on health information sensitivity in general, and their willingness to share such information to other parties. The study used qualitative research approach to collect empirical data and used themed interviews as the tool. Ten individuals who currently use an activity tracker were interviewed for the study. Privacy calculus model was used as a theoretical lens through out the study, which also guided the analysis of findings. The study found that individual’s don’t perceive the information collected by wearable devices as private or sensitive, but as general information. On the other hand, information in health records is considered to be very private and sensitive and much more specific, as they include additional personal information in written format. The study found that individuals do not share information from their wearable devices on social media. Users are willing to provide their information to doctors if it can be used in their health care. Individuals are also willing to provide their information for medical research and allow the device manufacturer to use the information for improving products and services. Even though the individuals are willing to share their information for different purposes, they had privacy concerns and worried how their information is used. They were concerned how information might spread to other parties and how it might be misused. Privacy concerns did not have a significant impact on the majority of the users as they accepted these risks. This thesis expands the previous research by presenting a new context in which privacy calculus theory can by utilized. Research findings have benefits for practice as the information collected with activity trackers can be utilized in the future for health care and research, since users are willing to share it.